2013
DOI: 10.4161/biom.25597
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-conjugated inhibitors of tumor necrosis factor-α for local control of inflammation

Abstract: Burns, chronic wounds, osteoarthritis, and uveitis are examples of conditions characterized by local, intense inflammatory responses that can impede healing or even further tissue degradation. The most powerful anti-inflammatory drugs available are often administered systemically, but these carry significant side effects and are not compatible for patients that have underlying complications associated with their condition. Conjugation of monoclonal antibodies that neutralize pro-inflammatory cytokines to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In addition, it has been found that polymers with conjugated inhibitors have a higher inhibitory effect on tumor necrosis factor-α (TNF-α) if the inhibitors are attached to higher-molecular-weight polymers; this is due to an increased diffusion time [39]. Since the binding of VEGF to highly sulfated fucans has been proven, a similar effect of increased diffusion time could play a role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that polymers with conjugated inhibitors have a higher inhibitory effect on tumor necrosis factor-α (TNF-α) if the inhibitors are attached to higher-molecular-weight polymers; this is due to an increased diffusion time [39]. Since the binding of VEGF to highly sulfated fucans has been proven, a similar effect of increased diffusion time could play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, a combination of antibodies to a polymer requires painstaking research. Whether the local neutralization of the inflammatory process will be effective in the human model is at this time unknown but at the same strategy is what makes this fascinating …”
Section: Introductionmentioning
confidence: 99%
“…Cross coupling and conjugation strategies are wildly applied to develop the modulator with multivalent and heterobifunctional constructs, which exhibit high affinity and specificity to the biomolecular target (Lambert, 2013 ; Washburn et al, 2013 ) (Figure 3C ). To date, there are limited examples targeting the AR with steroidal conjugates (Levine et al, 2014 ).…”
Section: Rational Antiandrogen Design To Circumvent Drug Resistance Dmentioning
confidence: 99%